2015
DOI: 10.1002/acr.22659
|View full text |Cite
|
Sign up to set email alerts
|

Use of Decision Support for Improved Knowledge, Values Clarification, and Informed Choice in Patients With Rheumatoid Arthritis

Abstract: Background The objective of this study was to examine the potential value of a theory-based, interactive decision support tool in clinical practice for patients with rheumatoid arthritis (RA) who are candidates for biologics. Methods We conducted an 8-week, 2-arm, parallel, single-blind, pilot trial in which candidates for treatment escalation with a biologic were randomized to receive a link to a web-based tool or to usual care. Outcomes included change in objective knowledge, subjective knowledge, value cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 26 publications
0
30
0
Order By: Relevance
“…However, the change in objective knowledge was significant only at 2 weeks and did not persist (Fraenkel, Matzko, et al, 2015b).…”
Section: Decision Aids For Biologic Taperingmentioning
confidence: 81%
See 2 more Smart Citations
“…However, the change in objective knowledge was significant only at 2 weeks and did not persist (Fraenkel, Matzko, et al, 2015b).…”
Section: Decision Aids For Biologic Taperingmentioning
confidence: 81%
“…A disconnect between patient satisfaction with therapy and physician disease and functional assessments has been observed, indicating that satisfaction with therapy involves much more than just achieving control of disease activity (Fraenkel, Seng, Cunningham, & Mattocks, ; Wolfe & Michaud, ). Concerns about adverse effects for any class of antirheumatic medication, negative impacts of treatments on quality of life, and loss of disease control are all notable concerns for people with RA, and there is a preference for accepting the status quo over changes to treatment that may lead to future improvement in disease control (Fraenkel, Matzko, et al, ; Wolfe & Michaud, ). It remains to be seen whether these broad concerns about tapering generalize to the scenario of tapering biologics or whether non‐adherence and decision‐making processes differ when faced with the option (or requirement) to taper biologics, given the relatively unique pattern of good adherence to these medications that involve patients continuing their biologic in the face of adverse effects (López‐González et al, ; Treharne, Lyons, Hale, Douglas, & Kitas, ; Vogelzang et al, ).…”
Section: Patient Perspectives On Tapering Biologicsmentioning
confidence: 99%
See 1 more Smart Citation
“…These assessments should ideally reflect theoretical mechanisms that are evidence-based. Here, we exploit research on memory representations of core valuescalled gist principles-that have been shown to guide decision making in multiple domains (e.g., Broniatowski, Klein, & Reyna, 2015;Fraenkel et al, 2012Fraenkel et al, , 2015Mills, Reyna, & Estrada, 2008;Reyna & Mills, 2014;Wolfe et al, 2015; for overviews, see Reyna, 2012;Reyna & Brainerd, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, consistent with prior gist-principles scales, we constructed a scale of simple values related to delay of gratification (e.g., Broniatowski et al, 2015;Fraenkel et al, 2012Fraenkel et al, , 2015Reyna, 2008;Reyna & Mills, 2014). We used money as a "common currency" to tap reward sensitivity (Levy & Glimcher, 2012), but, as we test in the second and third studies, we expected that these principles apply beyond problems with money to other problem behaviors.…”
Section: Introductionmentioning
confidence: 99%